cAMP post-transcriptionally diminishes the abundance of adrenodoxin reductase mRNA. - Brentano, S T (1992)
Adrenodoxin reductase (AR; ferridoxin: NADP+ oxidoreductase, EC 1.18.1.2) is a flavoprotein that mediates electron transport from NADPH to all known mitochondrial forms of cytochrome P450. AR mRNA was found in all human adult and fetal tissues examined; however, it was vastly more abundant in tissues that synthesize steroid hormones. The ratio of the 18- form of mRNA lacking 18 alternately spliced bases to the 18+ form was approximately 100:1 and remained constant irrespective of the tissue or hormonal manipulation, indicating that the alternate splicing is a passive nonregulated event. AR protein was unchanged by forskolin treatment of human JEG-3 cytotrophoblast cells for 24 h, but the mRNA diminished. Phorbol 12-myristate 13-acetate and cycloheximide had no effect, even though these agents had the expected effects on P450scc and adrenodoxin mRNAs. cAMP decreased the abundance of AR mRNA expressed from both transfected plasmids and the endogenous gene, indicating the effect was post-transcriptional. AR gene transcription in JEG-3 cells and promoter-chloramphenicol acetyltransferase constructs transfected into JEG-3 cells were unresponsive to forskolin. Powerful basal transcription elements were identified between -46 and -214 bases from the principal transcriptional initiation site, a region containing six elements closely resembling the binding site for transcription factor SP1.